Patologías en la cavidad oral de pacientes diagnosticados con discapacidad cognitiva en un Instituto prestador de servicios de salud (IPS) en Bucaramanga, Santander. (2020)
In this work, the dental conditions presented by patients with cognitive disabilities were identified according to the information provided in medical records. The objective of the research was to analyze the pathologies in the oral cavity of a group of patients with cognitive disabilities from an Institute providing health services in Bucaramanga. Materials and methods: A descriptive observational cross-sectional study was carried out, in which the data supplied from 35 medical records of people between 6 to 18 years diagnosed with cognitive disorders were analyzed; It was carried out by means of a data. Results: Of the information provided from the 35 medical records, according to an intraoral clinical examination, 71% (25) presented alterations in the oral mucosa; 31% (11) on the deep palate; he periodontal diagnosis was that they presented 69% (24) gingivitis associated with bacterial plaque; 13% (5) gingival inflammation without bleeding; COP 50 index carious lesions; 47 fillings; 1 missing tooth; ceo index 36 carious lesions; 6 teeth extracted; 16 dental fillings. Conclusion: People with cognitive disabilities present mostly bacterial plaque, which is related to poor oral hygiene. The presence of bacterial plaque, in turn, is related to the appearance of oral diseases such as dental caries and periodontal disease.